Airway Clearance and Pediatric Pulmonary Rehabilitation in Primary Ciliary Dyskinesia: A Clinical Framework for Children and Adolescents - Jiahui Zhao; Lina Chen; Wenhao Yang; Hanmin Liu (Journal of Clinical Medicine, 2026)
Primary ciliary dyskinesia (PCD) is an inherited motile-cilia disorder. Impaired mucociliary transport promotes persistent secretion retention, infection, inflammation, and bronchiectasis. The central treatment problem is therefore failure of airway clearance rather than infection alone. This narrative review evaluates airway clearance techniques (ACTs), mucoactive adjuncts, and pulmonary rehabilitation for children and adolescents. We prioritize direct pediatric PCD evidence, identify mixed-age or adult PCD findings as population-bound PCD evidence, and label pediatric bronchiectasis and cystic fibrosis evidence as indirect. Because no ACT has been shown to be universally superior and pediatric rehabilitation evidence remains limited, we present an author-proposed clearance-anchored dual-pillar framework. ACTs directly address mucus retention. Pulmonary rehabilitation complements ACT by targeting fitness, muscle performance, participation, and self-management. Response should be assessed across four domains: clinical stability, treatment performance, physiological and functional outcomes, and patient and family experience. Prospective multicenter comparative trials and harmonized pediatric outcome measures are urgently needed.